PERUBAHAN KECEPATAN ALIRAN AKIBAT VARIASI VOLUME VEGETASI DI BELOKAN SALURAN IRIGASI - Muhammad Nasir; Eldina Fatimah; Masimin Masimin (Prodi Magister Teknik Sipil Unsyiah, 2019)
D. I Timbang Deli is 520 Ha of flow area and 5000 meters of secondary channel is located in Deli Serdang Regency, North Sumatra Province. The turn of the irrigation network in overgrown vegetation on the cliffs and bottom of the channel, is expected to reduce the flow rate. The purpose of the study was to see the distribution of velocity, resistance and energy loss in the secondary channel due to vegetation. The method used is conducting surveys in the field by measuring water depth, vegetation volume and flow velocity. Trapezoidal channel with 36 m length, 1.45 lower width, 3.15 m upper width and 33,510 turn angle. The velocity measured in the middle and downstream regions across the channel is divided from points X1 to X5 with Q1 = 0.62m3/ sec and Q2 = 0.83 m3/sec. The results obtained in the speed distribution in Q1 Vmax mean X1 = 0.296 m/s and X5 = 0.199 m/s, the speed decreases due to the turn of 48.82%. On VV3 Vmaks the average is X4 = 0.216 m/sec and (X1 and X2) = 0,000 m/sec, the volocity decreases due to the presence of vegetation between X1, X2 and X5 at Q1 = 100%. In Q2 the average VV0 Vmax condition of the flow X1 = 0.477 m/s and X5 = 0.323 m/s between X1 and X5 the volocity decreases due to turn 28.45%. VV3 Vmax conditions on average X5 = 0.312 m / s and X1 = 0.000 m / s, between X1 and X5 the speed decreases due to the presence of 100% vegetation. In connection with the above results, with this research the local community and local government can carry out cleaning on the channel on a scale basis.